Development of Human Skin Equivalents with Inducible Ceramide Depletion for In Vitro Modeling of Lipid Impairment - Durotimi O. Dina; Miriam Maiellaro; Emanuela Camera; John T. Connelly (JID Innovations, 2025)
The lipid composition of the epidermis plays a critical role in the skin’s barrier function, and defects in lipid synthesis or assembly can cause a spectrum of skin diseases, ranging from dry skin to severe ichthyoses. The aim of this study was to develop an in vitro model of human skin with tunable inhibition of lipid synthesis. Human N/TERT keratinocytes were engineered to express doxycycline-inducible short hairpin RNAs targeting ceramide synthase 3, which is essential for synthesis of ultralong-chain ceramides and skin barrier function. We show that 3-dimensional human skin equivalents with induced knockdown of ceramide synthase 3 display normal stratification and terminal differentiation but have reduced Nile red staining for polar lipids. Further analysis of the lipidome by mass spectrometry confirmed a significant reduction in specific classes of ceramides and ceramide chain length in the ceramide synthase 3–depleted human skin equivalents. We also show that ceramide synthase 3 knockdown is reversible upon removal of doxycycline and can be used to study recovery and repair of epidermal lipids. Together, these findings provide an overall strategy for genetically regulating the lipid composition within human skin models and establish a tunable in vitro model of ceramide deficiency.